Non‐cooperative uplink interference protection framework for fair and energy efficient orthogonal frequency division multiple access networks. Issue 18 (1st December 2013) - Vaca Ramírez, Rodrigo A.; Thompson, John S.; Ramos Ramos, Víctor M.
Abstract : In this study, the authors consider a low complexity resource allocation scheme for reducing the uplink cochannel interference (CCI). The goal is to obtain improvements in energy efficiency by controlling the level of CCI affecting vulnerable mobile stations (MSs). This is done with a combined scheduler and a two layer power allocation scheme, which is based on non‐cooperative game theory. The authors approach forces users with good propagation conditions to reduce transmission power, to protect users experiencing high levels of interference. Thus, the MSs' uplink throughputs are equalised under the max–min fairness optimisation criterion. The scheme they propose works with minimum channel knowledge, since only base‐mobile channel path gains are required for the optimisation process. Furthermore, they show analytically and by simulation that the power reductions applied to users with good propagation conditions provide an increase in energy efficiency and fairness in the system. In addition, the simulation results show that their scheme provides a higher fairness index and a comparable system energy efficiency to a centralised signal interference noise ratio balancing scheme.